2007
DOI: 10.1359/jbmr.070726
|View full text |Cite
|
Sign up to set email alerts
|

Treatment With Anti-γ-Glutamyl Transpeptidase Antibody Attenuates Osteolysis in Collagen-Induced Arthritis Mice

Abstract: The effectiveness of a new antibody treatment on arthritis-associated osteolysis was studied by using CIA mice. GGT, a newly identified bone-resorbing factor, was upregulated in arthritic joints. We generated monoclonal antibodies against GGT and injected them into CIA mice. Mice treated with antibodies showed a reduction in osteoclast number and bone erosion.Introduction: ␥-Glutamyl transpeptidase (GGT) acts as a bone-resorbing factor that stimulates osteoclast formation. GGT expression has been detected in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…The injection itself caused tissue damage in the upper portion of periodontal tissue. Therefore, we used a cotton roll applicator saturated with stimulator to evoke tissue responses in rat periodontal tissue 10,36,37 . This method is useful because it avoids the tissue destruction caused by the application method itself.…”
Section: Discussionmentioning
confidence: 99%
“…The injection itself caused tissue damage in the upper portion of periodontal tissue. Therefore, we used a cotton roll applicator saturated with stimulator to evoke tissue responses in rat periodontal tissue 10,36,37 . This method is useful because it avoids the tissue destruction caused by the application method itself.…”
Section: Discussionmentioning
confidence: 99%
“…Ishizuka et al (2007) found that neutralizing antibodies against GGT had a therapeutic effect on joint destruction in collagen-induced arthritis in mice. Increased GGT activity was observed in serum and also in the synovial fluid of affected joints in patients with RA (Rambabu et al , 1990) and also in joints of AA-animals (Ponist et al , 2010).…”
Section: Discussionmentioning
confidence: 99%
“…GGT expression has been detected in active lymphocytes that accumulate at the inflammation region, as observed in RA. Ishizuka et al (2007) found that neutralizing antibodies against GGT had a therapeutic effect on joint destruction in collagen-induced arthritis in mice. Elevated expression and activity of GGT in joint tissue is a good marker for synovial inflammation and bone resorption.…”
Section: Adjuvant Arthritis: An Animal Model For Preclinical Evaluatimentioning
confidence: 99%